Alegoría E Ironía Bajo Censura En La Argentina Del Proceso (1976-1983). - Favoretto, Mara (Edwin Mellen Press, 2010)
This text offers an analysis of how rhetorical strategies such as allegory, irony and symbolism, were employed by dissenting Argentine writers and singer-songwriters during the military dictatorship that seized power on March 24th 1976.